The African State in a Changing Global Context: Breakdowns and Transformations - Búr, Gábor (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Edited by István Tarrósy, Loránd Szabó and Goran Hyden. LIT Verlag, Berlin–Münster, 2011. pp. 216.